The effectiveness of calcium silicate in preventing ice-ice disease and production performance of Kappaphycus alvarezii - Wirantari, Ayu Puspa; Nirmala, Kukuh; Supriyono, Eddy; Hamim, Hamim (Jurnal Akuakultur Indonesia, 2025)
The cultivation of Kappaphycus alvarezii faces serious challenges due to ice-ice disease outbreaks. This disease is caused by fluctuating environmental conditions that induce stress in the seaweed. Ice-ice disease is characterized by thallus whitening, softening, and fragility, which can lead to a reduction in yield and directly impact the economic returns for seaweed farmers. This study aims to evaluate the effectiveness of calcium silicate (CaSiO3) dosing as a mineral source for the prevention of ice-ice disease and the growth of K. alvarezii seaweed. The experimental design used was a completely randomized design with three replications across four treatments: CaSiO3 doses of 0, 1.6, 1.8, and 2 g/L. The study used an initial weight of K. alvarezii of 100 g per tie. The experiment was conducted through a field trial in seawater using an off-bottom cultivation method. The results indicated that the group with the highest dose of CaSiO3 (2 g/L) produced the best ice-ice resistance, with treatment D showing 17.77 ± 5.09% at the population level and 0.25 ± 0.015 at the individual level, which was statistically significant (P